The Effect of Health Belief Model Based Interventions on the Prevention of Pregnancy Anemia: Systematic Literature Review - Wafiq Aurelia Novany; Siti Aisah; Edy Soesanto (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Anemia during pregnancy remains a serious public health problem with significant adverse effects on both maternal and neonatal outcomes. Health Belief Model (HBM)–based interventions have the potential to improve anemia prevention behaviors by enhancing pregnant women’s knowledge, attitudes, perceptions, and adherence to preventive measures. Objective: This systematic review aimed to analyze the effects of HBM-based interventions on anemia prevention among pregnant women. Methods: A comprehensive literature search was conducted in PubMed, Scopus, ScienceDirect, ProQuest, and Google Scholar using English and Indonesian keywords based on the PICOT framework. Original studies published between 2015 and 2025 that evaluated HBM-based interventions for anemia prevention in pregnant women were included. The study selection process followed the PRISMA guidelines. Results: Ten studies were reviewed, consistently demonstrating that HBM- based interventions effectively improved maternal health outcomes. Significant increases in hemoglobin and hematocrit levels were observed, along with a reduction in anemia prevalence. Adherence to iron and folic acid supplementation (IFA/IFAS) increased by two to four times compared with control groups. Improvements were also found in knowledge, positive attitudes, perceived severity of anemia, and preventive behaviors, including increased iron and vitamin C intake and reduced tannin consumption. Interventions were delivered through intensive midwife-led counseling, illustrated modules, brochures, reminder SMS, messaging applications (MyPinkMom), and multicomponent nutrition education packages. Conclusion: HBM-based interventions are effective in improving hemoglobin levels, IFAS adherence, and anemia prevention behaviors among pregnant women. Integrating HBM-based education into antenatal care services, through both face-to-face counseling and digital media, is strongly recommended to reduce the prevalence of pregnancy-related anemia